Odpowiedzi

2010-02-02T13:27:25+01:00
A) 7x-3y= 5x-y -x+y
______ _____ _____ (*30)
5 3 2

3(x-1)=5(y+1)

30(7x-3y/5)=30(5x-y/3)-30(x+y/2)
3x-3=5y+5
6(7x-3y)=10(5x-y)-15(x+y)
3x=5y+8
42x-18y=50x-10y-15x-15y
3x=5y+8
42x-50x+15x=18y-10y-15y
3x=5y+8
7x=-7y
3x=5y+8
x=-1y
3(-1y)=5y+8
-3y=5y+8
-3y-5y=8
-8y=8
y=-1
x=-1*(-1)
x=1
y=-1

b) 2x-3y-1= x-5y - ½ (*2)
____
2

1¾-¼x= ³/₂y +¼

2(2x-3y-1/2)=2*x-2*5y-2*1/2
7/4-1/4x=3/2y+1/4

2x-3y-1=2x-10y-1
-1/4x=3/2y+1/4-7/4

-3y+10y=2x-1+1-2x
-1/4x=3/2y-6/4

7y=0
y=0
-1/4x=3/2*0-6/4
x=0-6/4*(-4)
x=0+6
x=6
y=0
2 3 2